(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Lepa is considered as an important and initial Chikitsa in reference with Vranashotha chikitsa described by Acharya Sushruta and when the Lepa is applied around the outer surface of eyes it is termed as Vidalaka. Vidalaka a type of Kriyakalpa therapy which is mainly indicated in acute inflammatory conditions of eyes such as Daha (burning sensation), Updeha (discharge), Ashru (watering) Shopha (swelling) and Raga (redness). Different formulations are given in classic texts for eye diseases and one among them is Yashtayadi lepa mentioned by Acharya Sharangadhara in Sharangadhara Samhita. It is described as Sarvanetrarujahara Yoga and consists Yastimadhu, Gairika, Saindhav, Daruharidra and Rasanjana as its main ingredients. Yashtyadi lepa was prepared as per the guidelines given for Lepa in API (Ayurvedic Pharmacopoeia of India) and analyzed using various standard physico-chemical parameters given for Lepa such as Loss on drying, Ash value, Water extract value, Alcohol extract value and pH. There is no standard guidelines is given for pharmaceutical analysis for Yastyadi Lepa in API. With this background the present study was undertaken to find pharmacognostical and physicochemical qualities of Lepa as recommended in Ayurvedic Pharmacopoeia of India (API) and to use them as reference for future studies on Yashtyadi Lepa for different ocular diseases.